PROFIL KECEMASAN PESERTA DIDIK DALAM BELAJAR DI KELAS VIII SMP NEGERI 23 PADANG - LIMDRI, AHMAD - (Bimbingan dan Konseling, 2014)
This research was motivated by the phenomenon of persistence of learners who hadexperienced anxiety in learning. The purpose of the research was description : the anxiety of studentsin learning in view of 1) phsyiological aspects and 2) psychological aspects. This research useddescriptive quantitative research which population in this research was the eight grade of Junior HighSchool 23 Padang who participants by 231 people. The samples were selected based on purposivesampling technique which amounts to 70 people. The source of data this research was data obtainedfrom the administration of Junior High School 23 Padang. The instrument of this research was aquestionnaire and the data processed by a percentage formula. The result of the research revealed thegeneral anxiety profile of learners in the classroom of Junior High School 23 Padang, include oncriterion sometimes anxious experience or they had anxiety in learning. The researcher recommendedthat the teachers of counseling in order to improve the serviles to help the students to cope an anxietythe learners in learning.